Changes of Benthic Macroinvertebrates in Thi Vai River and Cai Mep Estuaries under Polluted Conditions with Industrial Wastewater - HUONG, Nguyen Thi Thanh; DUC, Pham Anh; MIEN, Pham Van (GeoScience Engineering, 2017)
The pollution on the Thi Vai River has been spreading out rapidly over two recent decades caused by the wastewater from the industrial parks in the left bank of Thi Vai River and Cai Mep Estuaries. The evaluation of the benthic macroinvertebrate changes was very necessary to identify the consequences of the industrial wastewater on water quality and aquatic ecosystem of Thi Vai River and Cai Mep Estuaries. In this study, the variables of benthic macroinvertebrates and water quality were investigated in Thi Vai River and Cai Mep Estuaries, Southern Vietnam. The monitoring data of benthic macroinvertebrates and water quality parameters covered the period from 1989 to 2015 at 6 sampling sites in Thi Vai River and Cai mep Estuaries. Some basic water quality parameters were also tested including pH, dissolved oxygen (DO), total nitrogen (Tot_N), total phosphorus (Tot_P). The biodiversity indices of benthic macroinvertebrates were applied for water quality assessment. The results showed that pH ranged from 6.4 – 7.6 during the monitoring. The DO concentrations were in beetween 0.20 – 6.70 mg/L. The Tot_N concentrations ranked from 0.03 – 5.70 mg/L. The Tot_P concentrations were betwwen 0.024 – 1.380 mg/L. The benthic macroinvertebrate analyses showed that there were 36 species of polygochaetes, gastropods, bivalvians, and custaceans. Of which, species of polygochaetes were dominant in species number. The benthic macroinvertebartes density ranged from 0 – 2.746 individuals/m2 with the main dominant species of Neanthes caudata, Prionospio malmgreni, Prionospio sp., Disoma carica, Maldane sarsi, Capitela capitata, Terebellides stroemi, Bispira polymorpha, Grandidierella lignorum, Apseudes vietnamensis. The biodiversity index values during the monitoring characterized for aquatic enviornment conditions from mesotrophic to polytrophic. Besides, species richness positively correlated with DO, Tot_N, and Tot_P. The results confirmed the advantage of using benthic macroinvertebrates and their indices for water quality assessment.